ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI MERASIONALKAN BENTUK AKAR: Analysis of Students' Mathematical Communication Skills on the Material of Rationalizing Root Forms - Zafa, Pega Sabirah; Hasanuddin, Hasanuddin (Yayasan Al-Amin Qalbu, 2025)
The purpose of this study is to evaluate and understand students' ability to rationalize root forms and the elements that influence these abilities, so that it can provide a clear understanding of the level of students' mathematical communication skills in this material and as a reference in improving the mathematics learning process in the future. Educational activities carried out at one of Pekanbaru's high schools on December 1, 2023 were carried out well and efficiently. The method used to obtain information is a quantitative method. Data were collected by filling out question sheets by students. By using this method, researchers can conclude that educators have been able to carry out their duties well. The study shows that most students are quite successful in rationalizing root forms, but some still have difficulty in applying concepts and processes appropriately.